MRI DWI/ADC signal predicts shrinkage of lumbar disc herniation after O2–O3 discolysis. Issue 2 (April 2015) - Perri, Marco; Grattacaso, Giuseppe; Di Tunno, Valeria; Marsecano, Claudia; Di Cesare, Ernesto; Splendiani, Alessandra; Gallucci, Massimo
Purpose: Evaluate the discal morpho-structural changes as a predictive sign in the clinical outcome after ozone therapy in lumbar disc herniation using the T2–shine through effect in diffusion-weighted imaging (DWI). Method: One hundred and fifty-four patients suffering from lumbosciatica (89 men and 65 women; age range, 23–62 years) were included, previous MR study performed with FSE-T2 and T2-fat, SE-T1 and DWI sequences, and were randomly assigned to two groups. Seventy-seven patients (control group) underwent conservative treatment with intraforaminal injection of steroid and anaesthetic. The remaining 77 patients (study group) underwent the same treatment with the addition of oxygen–ozone (O2–O3). During the following six months, a MRI follow-up with the same sequences was performed. An intervertebral disc volumetric analysis (IDVA), DWI signal score and post treatment clinical outcome evaluation were performed for an assessment of hernia reduction. χ 2 test, Student's t test and analysis of covariance were used for comparison of variables. Results: In the study group, 58 of 77 patients had a successful outcome (responders). In the responders group, DWI T2–shine through effect was present during MRI follow-up and in particular in 53 of 77 patients in six months of follow-up ( p < 0.05). Moreover, in the same group a statistically significant disc shrinkage was shown by IDVA in sixth months of follow-up ( p < 0.05). Conclusions: T2–shine through effect in DWI is present before morphological disc reduction and moreover could be considered as a predictive sign of response to oxygen–ozone treatment.